Understanding the Patient 2.0: Gaining Insight into Patients' Rating Behavior by User-generated Physician Review Mining - Geierhos, Michaela; Bäumer, Frederik Simon; Schulze, Sabine; Klotz, Caterina (Modeling and Using Context. 9th International and Interdisciplinary Conference, CONTEXT 2015, Lanarca, Cyprus, November 2-6, 2015. Proceedings)
Patients 2.0 increasingly inform themselves about the quality of medical services on physician rating websites. However, little is known about whether the reviews and ratings on these websites truly reflect the quality of services or whether the ratings on these websites are rather influenced by patients’ individual rating behavior. Therefore, we investigate more than 790,000 physician reviews on Germany’s most used physician rating website jameda.de. Our results show that patients’ ratings do not only reflect treatment quality but are also influenced by treatment quality independent factors like age and complaint behavior. Hence, we provide evidence that users should be well aware of user specific rating distortions when intending to make their physician choice based on these ratings.
Keywords: Health 2.0; Rating Behavior; Patient Opinion Mining on Physician Rating Websites

What did you mean? Facing the Challenges of User-generated Software Requirements - Geierhos, Michaela; Schulze, Sabine; Bäumer, Frederik Simon (Proceedings of the 7th International Conference on Agents and Artificial Intelligence (ICAART), Special Session on Partiality, Underspecification, and Natural Language Processing (PUaNLP 2015))
Existing approaches towards service composition demand requirements of the customers in terms of service templates, service query profiles, or partial process models. However, addressed non-expert customers may be unable to fill-in the slots of service templates as requested or to describe, for example, pre- and postconditions, or even have difficulties in formalizing their requirements. Thus, our idea is to provide non-experts with suggestions how to complete or clarify their requirement descriptions written in natural language. Two main issues have to be tackled: (1) partial or full inability (incapacity) of non-experts to specify their requirements correctly in formal and precise ways, and (2) problems in text analysis due to fuzziness in natural language. We present ideas how to face these challenges by means of requirement disambiguation and completion. Therefore, we conduct ontology-based requirement extraction and similarity retrieval based on requirement descriptions that are gathered from App marketplaces. The innovative aspect of our work is that we support users without expert knowledge in writing their requirements by simultaneously resolving ambiguity, vagueness, and underspecification in natural language.

Zur affektiv-motivationalen Entwicklung von Lernenden im bilingualen Sachfachunterricht - Rumlich, Dominik (CLIL Revisited: Eine kritische Analyse des gegenwärtigen Standes des bilingualen Sachfachunterrichts)

Selbst(bestimmt) sind die Lernenden! Ideen und Methoden für eine studierendenzentrierte Lernveranstaltung. - Rumlich, Dominik (Diversität konkret)

Jürs-Munby, K. / Carroll, J. / Giles, S. (Hg.): Postdramatic Theatre and the Political - Tönnies, Merle (Journal of Contemporary Drama in English)

Between Authenticity and Objectification: Narrating the Self in Contemporary British Drama - Tönnies, Merle (Dramatic Minds. Performance, Cognition, and the Representation of Interiority)

‘Light of Life’: Gender, Place and Knowledge in H. G. Wells’ 'Ann Veronica' - Mildorf, Jarmila (Dark Nights, Bright Lights)

Worth Pursuing? The Limits of Cognitive Narratology - Mildorf, Jarmila (Književna istorija / Literary History)

Unreliability in Patient Narratives: From Clinical Assessment to Narrative Practice - Mildorf, Jarmila (Unreliable Narration and Trustworthiness: Intermedial and Interdisciplinary Perspectives)

Towards a Local Grammar-based Persondata Generator for Wikipedia Biographies - Geierhos, Michaela (Penser le Lexique-Grammaire)
Finding information about people in the World Wide Web is one of the most common activities of Internet users. It is now impossible to manually analyze all this information and new approaches are needed that are capable of processing the large-scale heterogeneous data in order to extract the pertinent information. The Wikipedia community still puts much effort in manually adding structured data to biographical articles, the so-called Persondata template. Thanks to this kind of metadata, semantically-enriched information concerning the biographee (e.g. name, date of birth, place of birth) can be extracted and processed by search engines. But it is a rather time-consuming task and users quite often forget to add this template: some biographies contain persondata, others do not. There is considerably less work done on developing approaches to automatically enhance English Wikipedia biographies with persondata and therefore improve the quality of structured user contributions. Within this paper, we describe our method to automatically generate persondata from biographical information in Wikipedia articles.

Comparative study on disambiguating acronyms in the scientific papers using the open knowledge base - Jeong, Do-Heon; Gim, Jangwon; Jung, Hanmin; Geierhos, Michaela; Bäumer, Frederik Simon (Conference Proceedings of the 9th Asia Pacific International Conference on Information Science and Technology (APIC-IST 2014))
In this paper, we focus on the acronym representation, the concept of abbreviation of major terminology. To this end, we try to find the most efficient method to disambiguate the sense of the acronym. Comparing the various feature types, we found that using single noun (NN) overwhelmingly outperformed noun phrase (NP) base. Moreover, the result also showed that collocation information (CL) was not efficient for enhancing performance considering a huge extra data processing. We expect to apply the open knowledge base Wikipedia to scholarly service to enhance the quality of the local knowledge base and to develop value-added services.

The same but not the same - Challenges in comparing patient opinions - Geierhos, Michaela; Schulze, Sabine (Challenges for Consumer Research and Consumer Policy in Europe)

Was beobachtet die Forschungsethik? Eine interdisziplinäre Diskussion zwischen Computerlinguistik und qualitativ-konstruktivistischer Sozialforschung - Geierhos, Michaela; Siri, Jasmin (Tagungsband Forschungsethik in der qualitativen und quantitativen Sozialforschung)

System Thinking: Crafting Scenarios for Prescriptive Analytics - Weber, Jens; Minhee, Cho; Lee, Mikyoung; Song, Sa-kwang; Geierhos, Michaela; Jung, Hanmin (Proceedings of the First International Workshop on Patent Mining and Its Applications (IPaMin 2014) co-located with Konvens 2014)
This paper focuses on the first step in combining prescriptive analytics with scenario techniques in order to provide strategicdevelopment after the useof InSciTe, a data prescriptive analytics application. InSciTe supports the improvement of researchers‘ individual performance by recommending new research directions. Standardized influential factors are presented as a foundation for automated scenario modelling such as the prototypical report generation function of InSciTe. Additionally, a use-case is shown which validatesthe potential of the standardized influential factors for raw scenario development.
Keywords: Standardized Influential Factors; Prescriptive Analytics; Role Model Group; Scenario Technique

SentiBA: Lexicon-based Sentiment Analysis on German Product Reviews - Dollmann, Markus; Geierhos, Michaela (Workshop Proceedings of the 12th Edition of the KONVENS Conference)
In this paper, we describe our system developed for the GErman SenTiment AnaLysis shared Task (GESTALT) for participation in the Maintask 2: Subjective Phrase and Aspect Extraction from Product Reviews. We present a tool, which identifies subjective and aspect phrases in German product reviews. For the recognition of subjective phrases, we pursue a lexicon-based approach. For the extraction of aspect phrases from the reviews, we consider two possible ways: Besides the subjectivity and aspect look-up, we also implemented a method to establish which subjective phrase belongs to which aspect. The system achieves better results for the recognition of aspect phrases than for the subjective identification.
Keywords: corpus linguistics; sentiment analysis

Linked Open Data System for Scientific Data Sets - Bäumer, Frederik Simon; Gim, Jangwon; Jeong, Do-Heon; Geierhos, Michaela; Jung, Hanmin (Proceedings of the First International Workshop on Patent Mining and Its Applications (IPaMin 2014) co-located with Konvens 2014)
In this paper, we present a system which makes scientific data available following the linked open data principle using standards like RDF and URI as well as the popular D2R server (D2R) and the customizable D2RQ mapping language. Our scientific data sets include acronym data and expansions, as well as researcher data such as author name, affiliation, coauthors, and abstracts. The system can easily be extended to other records. Regarding this, a domain adaptation to patent mining seems possible. For this reason, obvious similarities and differences are presented here. The data set is collected from several different providers like publishing houses and digital libraries, which follow different standards in data format and structure. Most of them are not supporting semantic web technologies, but the legacy HTML standard. The integration of these large amounts of scientific data into the Semantic Web is challenging and it needs flexible data structures to access this information and interlink them. Based on these data sets, we will be able to derive a general technology trend as well as the individual research domain for each researcher. The goal of our Linked Open Data System for scientific data is to provide access to this data set for other researchers using the Web of Linked Data. Furthermore we implemented an application for visualization, which allows usto explorethe relations between single data sets.
Keywords: Linked Open Data; Researcher Data; Acronym Data; D2R

A Technical Concept for Plant Engineering by Simulation-Based and Logistic-Integrated Project Management - Gutfeld, Thomas; Jessen, Ulrich; Wenzel, Sigrid; Weber, Jens (Proceedings of the 2014 Winter Simulation Conference)
Customized planning, engineering and build-up of factory plants are very complex tasks, where project management contains lots of risks and uncertainties. Existing simulation techniques could help massively to evaluate these uncertainties and achieve improved and at least more robust plans during project management, but are typically not applied in industry, especially at SMEs (small and medium-sized enterprises). This paper presents some results of the joint research project simject of the Universities of Paderborn and Kassel, which aims at the development of a demonstrator for a simulation-based and logistic-integrated project planning and scheduling. Based on the researched state-of-the-art, requirements and a planning process are derived and described, as well as a draft of the current technical infrastructure of the intended modular prototype. First plug-ins for project simulation and multi-project optimization are implemented and already show possible benefits for the project management process.

Prospective CLIL and non-CLIL students’ interest in English (classes): A quasi-experimental study on German sixth-graders - Rumlich, Dominik (Integration of theory and practice in CLIL)

Kamm, J. / Lenz, B. (Hg.): Representing Terrorism and Deconstructing Terrorism - Tönnies, Merle (Arbeiten aus Anglistik und Amerikanistik)

Wiki-Wonderland? – Eine Qualitative Analyse zu Vor- und Nachteilen von Wikis für Lehrende und Studierende - Flotmann, Christina (Lehr- und Lernpraxis im Fokus – Forschungs- und Reflexionsbeiträge aus der Universität Paderborn)

Political Rhetoric as a Structural and Ideological Instrument in Star Wars and Harry Potter - Flotmann, Christina (Politics in Fantasy Media: Essays on Ideology and Gender in Fiction, Film, Television and Games)

(En-)Gendering a Popular Theatrical Genre. The Roles of Women in Nineteenth-Century British Melodrama - Tönnies, Merle

Anti-hegemoniale Strategien des Kleinen. Britische dokumentarische Farbfotografie als Kritik des Thatcherismus - Tönnies, Merle (Kulturen des Kleinen. Mikroformate in Literatur, Kunst und Medien)

Book review: Daniela Carpi (ed.) (2011). 'Bioethics and Biolaw through Literature.'Berlin: de Gruyter - Mildorf, Jarmila (Anglistik)

Exploring ‘our pitiful attempts at connection’: Dialogue in Corey Mesler’s Novel 'Talk' - Mildorf, Jarmila (). Imaginary Dialogues in American Literature and Philosophy: Beyond the Mainstream)

Mapping Imaginary Dialogues in America - Kinzel, Till; Mildorf, Jarmila (Imaginary Dialogues in American Literature and Philosophy: Beyond the Mainstream)

Figurenrede im Roman aus kognitionslinguistischer und narratologischer Perspektive am Beispiel von Jean Rhys’ Roman "Good Morning, Midnight" - Mildorf, Jarmila (Germanisch-Romanische Monatsschrift)

Imaginary Dialogues in American Literature and Philosophy: Beyond the Mainstream

Magic, Science, Technology and Literature

Advertising in American Culture - Janzen, Olga

Gesprochene Korpora des Englischen und ihre Anwendung in der Grammatikforschung - Mindt, Ilka (Grundlagen einer sprachwissenschaftlichen Quellenkunde)

The benefits of comics for language learning at the lower secondary level: A practical approach - Rumlich, Dominik (Teaching comics in the foreign language classroom)

Students’ general English proficiency prior to CLIL: Empirical evidence for substantial differences between prospective CLIL and non-CLIL students in Germany - Rumlich, Dominik (Content and language integrated learning (CLIL) in Europe)

Using comics in the classroom - The obvious way of creating a favourable learning environment? - Deane, Neil; Rumlich, Dominik (Medien und Interkulturalität im Fremdsprachenunterricht: Zwischen Autonomie, Kollaboration und Konstruktion)

Middeke,M. / Schnierer, P.P. / Sierz, A. (Hg.): The Methuen Guide to Contemporary British Playwrights - Tönnies, Merle (Anglia)

Rossow, H. Globalismus und Lew Labour - Tönnies, Merle (Anglistik. International Journal of English Studies)

Baumbach, S. / Neumann, B. / Nünning, A.: A History of British Drama - Tönnies, Merle (Anglistik. International Journal of English Studies)

"This Bright Inward Cinema of Thought" – Stream of Consciousness in Contemporary English Fiction - Strauß, Sara

‘Monstrous’ Homes: How Private Spaces Shape Characters’ Identities in 19th-century Sensation Fiction - Flotmann, Christina (Monstrous Geographies: Places and Spaces of the Monstrous)

Ambiguity in ‘Star Wars’ and ‘Harry Potter’: A (Post-)Structuralist Reading of Two Popular Myths - Flotmann, Christina

Populäre Mythen bei Star Wars und Harry Potter - Flotmann, Christina
Interview 2 Feb. 2013

Northern Landscapes and Anti-Thatcherite Positioning - Tönnies, Merle (Journal for the Study of British Cultures)

Feminising a Classical Male Plot Model? Black British Women Writers and the 'Bildungsroman' - Tönnies, Merle (International Journal of English Studies)

Book review: Christoph Schubert (2009). 'Raumkonstitution durch Sprache: Blickführung, Bildschemata und Kohäsion in Deskriptionssequenzen englischer Texte.' Tübingen: Max Niemeyer - Mildorf, Jarmila (Informationsmittel für Bibliotheken)

Referential Frameworks and Focalization in a Craft Artist’s Life Story: A Socionarratological Perspective on Narrative Identity - Mildorf, Jarmila (Rethinking Narrative Identity: Persona and Perspective)

'Unnatural’ Narratives? The Case of Second-Person Narration - Mildorf, Jarmila (The Travelling Concepts of Narrative)

Teaching Medical Students about Medical Ethics and Domestic Violence: Alice Munro’s Short Story ‘Dimensions.’ - Mildorf, Jarmila (The Writing Cure: Literature and Medicine in Context)

The Writing Cure: Literature and Medicine in Context - Mildorf, Jarmila; Lembert-Heidenreich, Alexandra (The Writing Cure: Literature and Medicine in Context)

Studying Writing in Second Person: A Response to Joshua Parker - Mildorf, Jarmila (Connotations: Journal for Critical Debate)

Reading Fictional Dialogue: Reflections on a Cognitive-Pragmatic Reception Theory - Mildorf, Jarmila (Anglistik)